Bargaining and Wage Rigidity in a Matching Model for the US - James Malcomson; Sophocles Mavroeidis (Institute for the Study of Labor (IZA), 2015)
The Mortensen and Pissarides (1994) matching model with all wages negotiated each period is shown inconsistent with macroeconomic wage dynamics in the US. This applies even when heterogeneous match productivities, time to build vacancies and credible bargaining are incorporated. Wage rigidity consistent with micro evidence that wages of job changers are more flexible than those of job stayers allows the model to capture these dynamics and is not inconsistent with parameter calibrations in the literature. Such wage rigidity affects only the timing of wage payments over the duration of matches, so conclusions about characteristics based on calibrations continue to apply.
Keywords: E2; J3; J6; 330; matching frictions; wage bargaining; wage rigidity